CONTRIBUTION OF ANTIM IVERIELI AND MIHAI ISHTVANOVICH TO THE CAUSE OF THE ORGANIZATION OF THE GEORGIAN PRINTING HOUSE - Imerlishvili, Ivane (European Scientific Journal, ESJ, 2014)
In the paper the services of Antim Iverieli or Iberieli to his homeland Georgia are discussed, which are especially immense in the matter of the organization of the Georgian printing office. Antim Iverieli was born between the years of 1650-1660 and died in 1716. The King of the Georgians Vakhtang VI asked the Patriarch of Jerusalem to give him a helping hand in the organization of the printing office. The Patriarch of Jerusalim Crizanth Natharas forwarded the request of the King of the Georgians to Antim Iverieli to Rumania. As soon as Antim received the permission from the Rumanian ruler Constantin Brancoveanu (1688-1714) to render help to the King Vakhtang VI, he immediately sent to Tbilisi his best printer Mihai Ishtvanovich.